Social norms and perceptions of Saudis on active transportation - Hasan, Raed Abdullah; Alhomaidat, Fadi; Albdour, Mohammad S. (Frontiers in Built Environment, 2024)
The culture of active transportation (walking or cycling) in the Kingdom of Saudi Arabia (KSA) is less prevalent than in other societies. This study aims to understand the perceptions of people in the KSA about the role of cultural dimensions on active transportation. The study was conducted in Jeddah, prominent urban city in Saudi Arabia.The city suffers from rapid growth in vehicle users compared to active transportation. An online survey was employed with around 800 individuals participating from King Abdulaziz University. The results were analysed based on participants' sex. Few participants reported walking as the mode of transportation from home to work/school and no participants reported using a bicycle as daily commute. Females identify societal tradition and norms as the main factors that impede their engagement in active transportation. Males, who were embarrassed to walk/cycle, defined clothing and social status as the main barriers. Most males and females identify climate (high temperature throughout the year) as one of the main obstacles to walk/bike. Significant social, environmental, and infrastructural predictors of participants' modal choice were the distance from home to school/workplace, age, social values, family size, citizenship, and road safety.